Eksplorasi Preferensi Masyarakat Terhadap Pemanfaatan Ayam Lokal di Kabupaten Bogor Jawa Barat - Arma Aditya Kartika; Kanthi Arum Widayati; . Burhanuddin; Maria Ulfah; Achmad Farajallah (Jurnal Ilmu Pertanian Indonesia, 2016)
Indonesian native chickens consist of indigenous chickens and a chickens originated from abroad which adapted and grow in Indonesia. Based on 120 respondents who have been interviewed, there were seven types chicken commonly raised, namely: kampong, bangkok, arab, kate, pelung, gaga’, and birma. People commonly raised native chickens for religion, food, ornamental, and trading purposes. Six of those seven native chickens (86%) are reared for trading, five types (71%) for ornamental, and four types (57%) for egg and meat production purpose. Three types chicken (43%) were well-known had the benefits for eggs production. The religious category was the highest ICF value (1.00) followed by food (meat and eggs production) category with ICF value by 0.98. Arab chicken had the highest Fidelity Level (FL) value (70.96%) as egg and meat producer. Egg production of arab chicken reached 22.50 egg/period and it was the highest productivity of all experimental chickens. Average flock size per household was 11.31 with a population around 225 chickens/household. Kampong chicken was the most popular to be raised (79.16%) followed by bangkok (40.00%), kate (13.33%), gaga’ (10.00%), arab (8.33%), pelung (5.83%), and birma (3.33%). Kampong chicken is a food source and highly used for religion purpose had 38.23% of FL value